Pengaruh Pengawasan terhadap Disiplin Kerja Karyawan: (Studi pada PT. Swadharma Sarana Informatika Unit Kediri) - Nasyirudin, Muhammad; Novriharyaji, Dandhy; Wijaya, Hendra Agung (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2022)
An activity or organization is inseparable from supervisory activities. In an activity or organization, it relies not only on state of the art facilities and infrastructure or tools, but also the quality of its human resources. Surveillance activities are carried out in the hope of achieving the goals that have been planned. The purpose of the study was to see whether supervision had an influence on the work discipline of employees at PT Swadharma Sarana Informatika Unit Kediri. All 40 employees became a research sample. Researchers use quantitative methods with the main and supporting data being the source of the data used. The results showed that there was a significant influence of supervision on employee work discipline based on regression testing with the help of the SPSS program showing a signification value of 0.014 < 0.05.